Projek Sistem Pemulihan Pergelangan Tangan - Nor Mohamad, Amirrul Muhammad Shafie; Mohd Shaid, Muhamad Akif; Shamro, Muhammad Aiman (Multidisciplinary Applied Research and Innovation, 2023)
The wrist recovery system project was produced to restore the mobility of hand movements. This project was developed to improve hand rehabilitation methods more efficiently and interactively. The prototype hand rehabilitation system for wrist injuries consists of Arduino Uno, Arduino Joystick Module and Liquid Crystal Display (LCD). This prototype consists of eight LED units as direction indicators, where the patient has to move the joystick in the direction of the LEDs that have been set. The prototype also has three sets of intensive modules that patients can choose from as wrist mobility exercises. An Arduino Uno is used as a microcontroller to process the intensive module and provide instructions for the buzzer to sound if the patient successfully moves the joystick towards the designated LED. Menu instructions for intensive modules are displayed using LEDs and can be selected using switches. In conclusion, the buzzer will sound every time the patient successfully uses the wrist in the direction of the designated LED.